The genus Ontherus Erichson 1847 (Coleoptera: Scarabaeidae: Scarabaeinae): description of a new species, and notes on the genus in Colombia - González, Fabio Arturo; Medina, Claudia Alejandra U (Zootaxa, 2015)
The state of knowledge of the genus Ontherus Erichson 1847 in Colombia is reviewed and updated since the revision of the genus by Génier (1996), and the species list for Colombia of Medina et al. (2001). Two new distributional records for Colombia are confirmed; Ontherus politus Génier 1996 and Ontherus gilli Génier 1996. An updated species list of Ontherus for Colombia is presented with comments on the species with doubtful distribution in Colombia. O. felicitae n. sp., a new species from the mexicanus species group, is described from Western Andes of Colombia.